2020
DOI: 10.1186/s40168-020-00860-7
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of isoprene-degrading bacteria in phyllosphere and soil communities from a high isoprene-emitting environment: a Malaysian oil palm plantation

Abstract: Background: Isoprene is the most abundantly produced biogenic volatile organic compound (BVOC) on Earth, with annual global emissions almost equal to those of methane. Despite its importance in atmospheric chemistry and climate, little is known about the biological degradation of isoprene in the environment. The largest source of isoprene is terrestrial plants, and oil palms, the cultivation of which is expanding rapidly, are among the highest isoprene-producing trees. Results: DNA stable isotope probing (DNA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 75 publications
0
42
0
Order By: Relevance
“…Gordonia -like isoA sequences were found in poplar leaf samples, in oil palm leaves from this study (40% of sequences affiliated with Gordonia ) and Malaysian oil palm leaves (over 98%) [ 29 ]. In a similar DNA-SIP experiment, enriching leaves and soil from a Malaysian oil palm tree, Carrión et al showed the presence of Gordonia and members of the Sphingomonadaceae family enriched in the soil and phyllosphere communities [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gordonia -like isoA sequences were found in poplar leaf samples, in oil palm leaves from this study (40% of sequences affiliated with Gordonia ) and Malaysian oil palm leaves (over 98%) [ 29 ]. In a similar DNA-SIP experiment, enriching leaves and soil from a Malaysian oil palm tree, Carrión et al showed the presence of Gordonia and members of the Sphingomonadaceae family enriched in the soil and phyllosphere communities [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…New understanding of the physiology, biochemistry, and molecular biology of isoprene metabolism has provided the tools for designing functional gene primers and probes based on isoA, encoding a key component of the IsoMO [ 19 , 29 ]. Surveys with samples from the terrestrial environment, mainly soils and the phyllosphere have revealed the presence of isoprene-degrading bacteria, especially in environments containing trees that produce high concentrations of isoprene [ 19 , 25 , 27 , 29 , 30 ]. DNA-stable isotope probing (DNA-SIP) experiments have also revealed the diversity of active isoprene degraders present in these environments, which are often Actinobacteria, especially Rhodococcus species, but also include other Gram-negative isoprene degraders [ 19 , 25 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…They also demonstrated that isoprene-degrading bacteria isolated from these environments consumed isoprene naturally produced by microalgal cultures. More recently, experiments conducted with phyllosphere samples from high isoprene-emitting trees from temperate and tropical regions (poplar, willow, and oil palm trees) have shown that this environment is likely to be an important source of isoprene-degrading microorganisms [42][43][44][45]. However, despite these findings, the significance of the biological consumption of isoprene is still a key aspect of the global isoprene cycle that needs to be addressed.…”
Section: Biological Sinks For Isoprenementioning
confidence: 99%
“…Isoprene enrichments with garden and tyre dump soils, as well as soils in the vicinity of willow trees, have also led to the isolation of several Rhodococcus species and novel Nocardioides, Ramlibacter, and Variovorax strains, which degrade isoprene [51][52][53][54][55][56]. Recent studies exploring the phyllosphere of poplar, willow, and oil palm trees have shown that this environment harbours a considerable variety of isoprene-degrading isolates, including members of the genera Rhodococcus, Gordonia, Sphingopyxis, and Variovorax [42,51,52,55]. Moreover, Acuña Alvarez et al [41] reported the isolation, from marine and estuarine environments, of several Actinobacteria (Leifsonia, Gordonia, Mycobacterium, Rhodococcus) and Alphaproteobacteria (Stappia, Loktanella, Shinella) that could grow on isoprene, with Gordonia and Mycobacterium being the most well characterised [57].…”
Section: Diversity Of Isoprene-degrading Bacteriamentioning
confidence: 99%
See 1 more Smart Citation